2019
DOI: 10.3390/ma12162577
|View full text |Cite
|
Sign up to set email alerts
|

Mix Design and Mechanical Properties of High-Performance Pervious Concrete

Abstract: The mechanical properties of traditional pervious concrete are insufficient, which limits its application. In view of the imperfections of traditional permeable concrete in mechanics, this paper aimed to find a suitable material composition that can be used as a feasible mix design of high-performance pervious concrete, to essentially improve its mechanical properties. Based on the view that concrete is a two-phase material, in order to understand the rheological properties of the matrix, it was subjected to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…After designing the concrete mix composition and laboratory tests, the last part of the process is preparing a working recipe for 1 m 3 of concrete mix. It is also vital to consider the recipe changes that may result from the dampness of the aggregate and adapt it to individual conditions, such as the capacity of a transport vehicle [ 29 , 30 ].…”
Section: Concrete MIX Design and Machine Learningmentioning
confidence: 99%
“…After designing the concrete mix composition and laboratory tests, the last part of the process is preparing a working recipe for 1 m 3 of concrete mix. It is also vital to consider the recipe changes that may result from the dampness of the aggregate and adapt it to individual conditions, such as the capacity of a transport vehicle [ 29 , 30 ].…”
Section: Concrete MIX Design and Machine Learningmentioning
confidence: 99%
“…Pore area mm 2 � Pore area pixel 2 • 100 × 100 mm 2 1000 × 1000 pixel 2 , To facilitate the description of the pore morphology, the pores are simplified to a circular and an elliptical shape as described by the equivalent diameter and roundness, respectively. e equivalent diameter (D e ) of a single pore is calculated as follows:…”
Section: Planar Porositymentioning
confidence: 99%
“…ey found that there is a close correlation between porosity, permeability, and mechanical properties of pervious concrete. In the studies of Debnath and Sarkar [1] and Tang et al [2], they found that the presence of fine aggregates hindered the formation of pores, and the single size aggregate could increase the permeability. e porosity and pore features of pervious concrete are important to the permeability and mechanical properties [3]; thus, porosity ranging from 15% to 25% was recommended [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, this type of concrete has mechanical strengths, including compressive, flexural, and splitting tensile strengths which are less than that of the normal concrete, because of the absence of fine aggregate and large voids. This leads to boost porosity and limits the application of pervious concrete 11–16 …”
Section: Introductionmentioning
confidence: 99%